Reinforced brick-masonry light vaults: semi-prefabrication, construction, testing and numerical modeling - López-Almansa, F. (2010)
This work deals with short to mid span-length light vaults made of reinforced brick-masonry. The research is oriented at proposing semi-prefabrication and construction techniques. Numerical models for predicting the structural behavior of this type of structures are developed. Experimental research is performed with the following three main objectives: (i) validating the proposed construction techniques, (ii) investigating the structural performance, and (iii) calibrating the numerical models. The obtained results show that the proposed techniques are feasible, and that the structural behavior is adequate in terms of ductility and of strength. The structural system can be modeled with the developed numerical tools.